The Use of DNA Markers in Rice Breeding for Blast Resistance and Submergence Tolerance as a Weed Control Factor - Elena Dubina; Pavel Kostylev; Yulia Makukha; Margarita Ruban (Plants, 2025)
Diseases and weeds occupy a leading place among the factors limiting the yield of agricultural crops, including rice. These factors can be overcome through the use of chemical protective agents, as well as through the creation and introduction into agricultural production of rice varieties resistant to these stressors. The use of DNA marking technologies for target genes of economically valuable traits in the creation of promising varieties allows not only for the identification of genes but also the monitoring of their transmission during crosses and the selection of breeding-valuable genotypes with genes of interest. In addition, this ensures a reduction in the volume of breeding nurseries, as well as time and material costs during variety modeling, and rapid rotation of new high-yield varieties with specified characteristics. We have selected effective marker systems based on the use of DNA marking technologies for target genes for resistance to blast (Pi) and submergence tolerance (Sub1A). These systems allow for precise targeted selection of hybrid plants with these genes in the breeding process. In addition, we have automated the detection of transferred Pi-ta and Pi-b genes, which greatly relieves the DNA analysis during mass screening of breeding material. The final result of this work is the created rice varieties Al’yans, Lenaris and Kapitan with the Pi-ta blast resistance gene and the Pirouette rice variety with the Pi-1, Pi-2, and Pi-33 genes. These varieties exceed the standards by 0.64–2.2 t/ha, and their involvement in production makes it possible to obtain additional products by increasing yields in the amount of about RUB 80 thousand/ha.